Предмет: Алгебра,
автор: yarinayankovskі
спростити вираз
1) (3m – 2n)2 + 12mn;
2) (2а – b)(а + b) + b2;
3) (3 – а)(3 + а) + (1 – а)2;
4) (2х – 7у)2 + (2х + 7у)2 – 8х2;
5) (2 – 3b2)(3b2 + 2) + (b2 – 1)2;
6) (2 – b2)(2 + b2)(4 + b4)(16 + b8).
Ответы
Автор ответа:
0
1) (3m – 2n)² + 12mn=9m²-6mn+4n²+12mn=9m²+4n²;
2) (2а – b)(а + b) + b²=2a²+2ab-ab-b²+b²=2a²+ab;
3) (3 – а)(3 + а) + (1 – а)²=9-a²+1-2a+a²=10-2a;
4) (2х – 7у)² + (2х + 7у)² – 8х²=4x²-28xy+49y²+4x²+28xy+49y²-8x²=98y²;
5) (2 – 3b²)(3b² + 2) + (b² – 1)² =4-9b⁴+b⁴-2b²+1 = -8b⁴-2b²+5 ;
6) (2 – b²)(2 + b²)(4 + b⁴)(16 + b⁸)=(4-b⁴)(4 + b⁴)(16 + b⁸)=(16-b⁸)(16+b⁸)=256-b¹⁶.
2) (2а – b)(а + b) + b²=2a²+2ab-ab-b²+b²=2a²+ab;
3) (3 – а)(3 + а) + (1 – а)²=9-a²+1-2a+a²=10-2a;
4) (2х – 7у)² + (2х + 7у)² – 8х²=4x²-28xy+49y²+4x²+28xy+49y²-8x²=98y²;
5) (2 – 3b²)(3b² + 2) + (b² – 1)² =4-9b⁴+b⁴-2b²+1 = -8b⁴-2b²+5 ;
6) (2 – b²)(2 + b²)(4 + b⁴)(16 + b⁸)=(4-b⁴)(4 + b⁴)(16 + b⁸)=(16-b⁸)(16+b⁸)=256-b¹⁶.
Похожие вопросы
Предмет: Українська мова,
автор: arsenkovbel20
Предмет: Математика,
автор: feniks6197
Предмет: Математика,
автор: paulsyrtsev
Предмет: Математика,
автор: krasavitca0320
Предмет: Литература,
автор: kraineva2014